Характеристики концепта «Образование» - Chaklikova, Assel; Zhakyanova, Aygerim (Journal of Educational Sciences, 2017)
This article is devoted to understanding of the basic ideas about the “Education” concept in a scientific environment in conditions of internationalization. The author focuses on the need for the development of a national model of education, that should combine the international standards and the local standards in a qualitative way. The formation of a new educational paradigm presupposes the solution of a number of basic contradictions between the developing culture and the traditional way of human education, between the integrity of culture and the branch principle of its representation through a variety of subject areas in education. Integration of Kazakhstan into the world educational space (the Bologna process) raises the issue of the unification of the education program on the National Education System. In this regard, the conceptual analysis of education is of great importance: education activity, values and objectives that determine the content and direction of education development. The goals and values of education are defined and updated taking into account the actual demands of the society. For the future of society, the three education goals still remain important: they are personal development, active participation of the individual in the society, and vocational training. Modernization of the national education system should take into account the opportunities and resources of the state, as well as the modern trends in education system. Key words: education, national model of education, the aim of education, international education.